2015
DOI: 10.1016/j.carres.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of nucleobase-modified UDP-sugars: scope and limitations

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The reaction reached completion when signals for CTP (−5.83 ppm, doublet, −10.75 ppm, doublet, −19.38 ppm, triplet) had diminished. At this point, CMP–Kdn was purified using strong anion exchange as outlined in Wagstaff et al ( 64 ). 1 H NMR, 31 P NMR, and MS values aligned well with previously described literature ( 21 , 65 ) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction reached completion when signals for CTP (−5.83 ppm, doublet, −10.75 ppm, doublet, −19.38 ppm, triplet) had diminished. At this point, CMP–Kdn was purified using strong anion exchange as outlined in Wagstaff et al ( 64 ). 1 H NMR, 31 P NMR, and MS values aligned well with previously described literature ( 21 , 65 ) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, Field et al reported a one-pot multienzyme approach to base modified UDP-Glc and UDP-Gal (Scheme 3). 8 This provided enzymatic access to a new class of 5-position modified sugar-nucleotides, which had previously demonstrated promise as GT inhibitors 9 and as fluorescent tools for GT assay development. 10 Their strategy employed a small panel of 5position modified UTPs and Glc 1-phosphate, incubated with UDP-glucose pyrophosphorylase (GalU) to generate, in situ, a modified UDP-Glc in catalytic quantity, to be continuously recycled by GalU.…”
Section: Towards Udp and Dtdp Sugar-nucleotidesmentioning
confidence: 99%
“…However,i ng eneral, low yields (5-23 %) were obtained and the conversion of the gluco compounds into the corresponding galacto derivatives was the problematic step. [68] As lightly modified strategy was employed for the preparation of UDPÀGal analogues 80 and 81.I odination of UMP 76 afforded 5-iodo derivative 64,w hichw as transformed into key intermediate 69.M orpholidate 69 was submitted to aS uzuki-Miyaura cross-coupling reactionwith the corresponding boronic acid to furnish compounds 77 and 78,w hich were coupled with d-galactose phosphate to afford compounds 79 and 80, respectively (Scheme12). [69] By comparing the inhibitory activities of compounds 79 and 80 towards a-a nd b-(1,4)GalTsw ith those of 5-substitutedu ridine derivatives 81 and 82 ( Figure 10), which had been prepared from 5-iodouridine 63,i tw as clear that derivatives that incorporated the sugardiphosphate unit improved the results.…”
Section: Modification At the Nucleobasementioning
confidence: 99%